Biharmonic reeb curves 3-dimensional kenmotsu manifold - Körpinar, Talat; Turhan, Essin (My University, 2011)
The present paper deals with the study of biharmonic Reeb curves in 3-dimensional Kenmotsu manifold. We characterize curvatures of biharmonic Reeb curves in 3-dimensional Kenmotsu manifolds. Moreover, we apply biharmonic Reeb curves in special 3-dimensional Kenmotsu manifold K. Finally, we characterize the biharmonic Reeb curves in terms of their curvature and torsion. © IDOSI Publications, 2011.
Keywords: Biharmonic curve; Kenmotsu manifold; Reeb vector